From motherhood to activism: a history of women in transformation - Orhan, Gözde. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2008., 2008)
This study scrutinizes the mobilization of mothers in Turkey whose children were subjected to state violence or to abuse of rights for a variety of reasons, relying on the “natural” legitimacy rooted in being a mother, and their entrance into the political sphere with which they had not been familiar. How individual attempts having the aim of saving / finding a child evolved towards collective action, how the pain experienced brought women a collective identity, and how the struggle process transformed the mentality of the mothers are the basic questions of this study. Considering clear and hidden forms of resistance special to motherhood, how the title of “mother,” which serves to confine women in the home and which is shown as the reason for woman’s oppression by some feminists was used as the “weapon of the weak” by the mothers and how it led to reverse their disadvantageous position in the public sphere are analyzed. The study, which examines the way of organization, the demands, and the dynamics of the motherist movements in Turkey by classifying those in four periods, highlights the contribution of the motherist movements to the struggle of human rights.
Keywords: Women political activists.